Exploring the excited structure of 11Li through (t,p) reactions at the upgraded SEC Device - Ruiz D. Fernandez; Borge M.J.G; Tengblad O.; Fynbo H.; Riisager K. (EPJ Web of Conferences)
11Li is the best example of a two-neutron (2n) halo nucleus, a system where the last nucleons, due to the low binding energy and angular momentum, spend a large part of their time far from the core. Despite extensive experimental efforts, its excited structure remains a topic of debate. Experiment IS690 employs a novel approach to investigate the excited states of 11Li, directly populating these states via the (t,p) reaction from the less exotic 9Li nucleus. In this contribution the experimental setup and preliminar results are summarised.